Perancangan Jalur Gelombang Mikro 13 Ghz Titik Ke Titik Area Prawoto–Undaan Kudus - Imam Santoso; Ajub Ajulian Zahra; Al Anwar (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
In communication systems, transmission lines have the important role as the link media for connecting data from source to destination. One of information transmission using unguided media or wireless in point to point connection is microwave system. The succesfull in receiving information data with microwave communication system depend on the accurate parameters value of the radio link budget, including the prediction of minimum receive signal level and all possible environment disturbances. In this research we using the Pathloss software as a tool to get all the link budget parameters values, such as operating frequency, point-to-point distance, transmitter power, and antenna diameter. The link budget design will be implemented in point-to-point microwave radio link from Prawoto to Undaan Sites in Kudus area of Central Java.As a result with the point-to-point distance of 6,62 km, the optimum parameters of 13 GHz microwave radio link used SP4-127 antenna with 1,2m in diameter, with transmitter power 24 dBm and receive signal level -25,90 dBm.Keywords: point-to-point microwave radio link, link budget, pathloss